Semiotic analysis in the novel Anak Rembulan as an alternative creation of learning materials for short story writing for grade VI elementary school students - Maharani, Sofy; Wardana, Deni; Maulana, Farid Rizqi (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Language is a very important means of communication in daily life, including when learning a language. The four language skills, namely listening, speaking, reading, and writing, support each other in the effective communication process. In Indonesian learning in grade VI with the Independent Curriculum, students must be able to write texts according to the applicable linguistic rules and social norms. In this context, the researcher chose the novel Anak Rembulan by Djokolelono. The novel was chosen as a medium to help students write short stories. The author conveys his feelings through a system of signs that can be analyzed with a semiotic approach to reveal hidden meanings. The research methodology uses a synchronous approach, namely language research that is comparable to qualitative. The research technique is divided into two, namely data collection and data analysis. Based on Peirce’s theory of semiotics, this research focuses on the icons, indexes, and symbols contained in the novel. This research aims to find out the semiotic elements in the novel Anak Rembulan which later the results of this research can be used as an alternative in making learning materials to write creative and meaningful short stories. This study uses a synchronous research design and content analysis method. Based on the results of the analysis, it was found that the semiotic element of the icon category in the novel contained 17 data. The index category in the novel has 56 data and the symbol category in the novel has 67 data. The results of the research will be used as a teaching module in short story learning for grade VI elementary school students